Latitudinal Variance in the Drivers and Pacing of Warmth During Mid‐Pleistocene MIS 31 in the Antarctic Zone of the Southern Ocean. Issue 8 (15th August 2022) - Warnock, Jonathan P.; Reilly, Brendan T.; Raymo, Maureen E.; Weber, Michael E.; Peck, Victoria; Williams, Trevor; Armbrecht, Linda; Bailey, Ian; Brachfeld, Stefanie; Du, Zhiheng; Fauth, Gerson; García, Marga M.; et al.
Abstract: Early Pleistocene Marine Isotope Stage (MIS)‐31 (1.081–1.062 Ma) is a unique interval of extreme global warming, including evidence of a West Antarctic Ice Sheet (WAIS) collapse. Here we present a new 1, 000‐year resolution, spanning 1.110–1.030 Ma, diatom‐based reconstruction of primary productivity, relative sea surface temperature changes, sea‐ice proximity/open ocean conditions and diatom species absolute abundances during MIS‐31, from the Scotia Sea (59°S) using deep‐sea sediments collected during International Ocean Discovery Program (IODP) Expedition 382. The lower Jaramillo magnetic reversal (base of C1r.1n, 1.071 Ma) provides a robust and independent time‐stratigraphic marker to correlate records from other drill cores in the Antarctic Zone of the Southern Ocean (AZSO). An increase in open ocean species Fragilariopsis kerguelensis in early MIS‐31 at 53°S (Ocean Drilling Program Site 1, 094) correlates with increased obliquity forcing, whereas at 59°S (IODP Site U1537; this study) three progressively increasing, successive peaks in the relative abundance of F. kerguelensis correlate with Southern Hemisphere‐phased precession pacing. These observations reveal a complex pattern of ocean temperature change and sustained sea surface temperature increase lasting longer than a precession cycle within the Atlantic sector of the AZSO. Timing of an inferred WAIS collapse is consistent with delayed warmth (possibly driven by sea‐ice dynamics) in the southern AZSO, supporting models that indicate WAIS sensitivity to local sub‐ice shelf melting. Anthropogenically enhanced impingement of relatively warm water beneath the ice shelves today highlights the importance of understanding dynamic responses of the WAIS during MIS‐31, a warmer than Holocene interglacial. Plain Language Summary: Sea level rise and other impacts resulting from loss of ice from the Antarctic Ice Sheet due to climate change are a significant societal concern. Studying past periods of ice loss can help to predict future ice loss and understand the types of conditions that result in massive ice loss. Marine Isotope Stage 31, a past period of significant Antarctic ice loss, is studied using diatoms, fossil algae. Evidence of sea surface warming leading to Antarctic ice loss is identified. These data also reveal a more complex timing of warming than has been previously recognized across the Southern Ocean. Warmth affects the northern parts thousands of years before more southerly regions. Additionally, northern parts of the Southern Ocean are seen to be controlled by different orbitally driven climate factors than southern parts. The study highlights the importance of warm Southern Ocean water on future ice mass loss. Key Points: Evidence of Southern Ocean surface warming and West Antarctic Ice Sheet mass loss during Marine Isotope Stage‐31 is observed Obliquity pacing of warmth is observed in the northern Antarctic Zone of the Southern Ocean (AZSO); precession pacing is observed in the south Warm conditions are observed in the northern AZSO thousands of years before the south